Cluster munitions and international law : disarmament with a human face? - Breitegger, Alexander (Abingdon, Oxon : Routledge, 2012)
'This book offers a comprehensive argument for why pre-existing international law on cluster munitions was inadequate to deal with the full scope of humanitarian consequences associated with their use. The book undertakes an interdisciplinary legal analysis of restraints and prohibitions on the use of cluster munitions under international humanitarian law, human rights law, and international criminal law, as well as in relation to the recently adopted Convention on Cluster Munitions (CCM). The book goes on to offer an in-depth substantive and procedural analysis of the negotiations which led to the 2008 CCM, in part based on the author's experiences as an adviser to Cluster Munitions Coalition-Austria. Cluster Munitions and International Law is essential reading for practitioners and scholars of International Law, including International Humanitarian, Human Rights, International Criminal or Disarmament Law and anyone interested in legal and humanitarian perspectives on cluster munitions legislation and policy. It is unique in bringing a practitioner's perspective to a scholarly work'--Provided by publisher.
5.The use of cluster munitions as a human rights problem -- 5.1.The relationship between IHL and human rights law -- 5.2.The application of the right to life to cluster munition use during armed conflict -- 5.3.The application of the right not to be subjected to cruel or inhuman treatment to cluster munition use during armed conflict -- 5.4.The application of the right to life to victims of unexploded sub-munitions -- 5.5.The application of social, economic and children's rights to contamination with unexploded sub-munitions -- 5.6.The Ottawa Convention on anti-personnel mines -- 5.7.The Convention on the Rights of Persons with Disabilities -- 6.Issues related to cluster munition use before human rights mechanisms -- 6.1.The Behrami case before the European Court for Human Rights -- 6.2.The UN special procedures on the use of cluster munitions in Lebanon and Israel -- 7.The Oslo process on cluster munitions and its interaction with the CCW -- 7.1.The Third Review Conference of the CCW -- 7.2.The Oslo Conference on cluster munitions -- 7.3.The Lima Conference on cluster munitions -- 7.4.The Vienna Conference on cluster munitions -- 7.5.The Wellington Conference on cluster munitions: towards the Wellington Declaration -- 8.The Convention on Cluster Munitions -- 8.7.Interoperability -- 8.2.The definition of prohibited cluster munitions -- 8.3.Stockpile destruction -- 8.4.Clearance and destruction of cluster munition remnants and risk reduction education -- 8.5.Victim assistance -- 8.6.The issue of financing cluster munition producers -- 9.Conclusions.
Includes bibliographical references (p. [248]-259) and index.
Keywords: Cluster bombs (International law)